Group Identities in Conflicts - Andreas Wagener; Martin Kolmar (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We analyze the interplay of group identity and inter-group conflict in a contest where each of two conflicting groups can develop either a group or an individualistic identity. Contest structures impact on the adoption of identities which themselves influence behavior in the contest. We show the following: If group sizes and contest technologies are similar, group identities emerge. This then results in a reduced well-being for all individuals. If one group has a large advantage in the contest, only this group will create a group identity and benefit on the expense of the other. Outgroup hostility favors asymmetric identities. Several applications of the findings are discussed.
Keywords: D74; H41; D02; 330; Contests; Public Goods; Social Identity